Pemberdayaan Industri Kecil Menengah Pangan di Kelurahan Air Raja, Kecamatan Tanjungpinang Timur, Kota Tanjungpinang - Natasyaputri Sendhe Siregar; Nazaki Nazaki; Novi Winarti (Social Issues Quarterly, 2023)
The Empowerment of Food Small and Medium Industries (IKM) aims to increase the competitiveness of food IKM actors in the Air Raja Village. However, until now there are still obstacles in carrying out marketing and promotion of IKM products in Tanjungpinang City, especially in Air Raja Village. This study aims to determine Empowerment of Small Food Industries in Air Raja Village. The empowerment process that looks at three things, namely development, empowerment and the creation of independence that occurs in Air Raja Village. The method in this study used a qualitative descriptive method with a total of 7 (seven) informants, and used data collection techniques in the form of interviews and documentation. The results of this study indicate that the empowerment of food IKM carried out in the Air Raja Village has not been successful. Furthermore, from the indicators of creating independence, the empowerment carried out by the Disdagin has had a positive impact on food IKM actors themselves who have become independent and have made it easier for actors to increase economic needs, seen from the small initial capital and after being independent, the income of IKM has increased. Because the quality is carried out in accordance with the standards required by the government.